Evaluation Of Integration Of Environmental Knowledge In Biology Subjects To Strengthen The Environment Literacy Of Learners In High School - Dewi, Rahma; Hadiansyah, Yudi; Masduki, Masduki; Khairiyah, Khairiyah (Jurnal Rekayasa Teknologi dan sains, 2024)
ABSTRACT Since 1989, environmental education has been integrated into all subjects at all levels of primary and secondary education, one of which is Biology. However, until now, the learning outcomes of environmental education have not been widely felt, especially in changes in knowledge, attitudes, and behavior (environmental literacy). This study aims to determine whether environmental education materials integrated with biology subjects strengthen students' environmental literacy. Based on this, a study was conducted to analyze students' knowledge, attitudes, and behavior (environmental literacy) that have obtained environmental materials integrated with biology subjects. The research was conducted by identifying the syllabus and lesson plans for biology subjects and evaluating environmental education materials; then, students were given a questionnaire divided into three groups of questions according to environmental literacy standards: knowledge, attitudes, and behavior towards the environment. The research sample was 84 students from grades X and XII. The analysis results show that integrating environmental education materials in biology subjects does not strengthen the students' environmental literacy. These results can be interpreted that integrated environmental education materials need to be deepened, curriculum design, teaching method innovation, and learning media. Keywords: integration of environmental knowledge, biology subject, environment education, environmental literacy.